Kontekstualisasi Rahmah Dalam Q.S Ar-Rum [30]:21 Terhadap Pasangan Childfree dan Childless - Siti Melati; Akhmad Dasuki; Munirah Munirah (NALAR, 2023)
This study examines the contextualization of the term rahmah in surah ar-Rum verse 21 on the issue of childfree and childless to find a broader interpretation. This type of research is qualitative and library research, namely data collection through literature review. Then, the data obtained were analyzed using the descriptive-analysis method, namely describing the data obtained, then analyzed using Fazlur Rahman's Double Movement theory. This research resulted in the finding that childfree and childless can achieve a gracious marriage even though they do not have children because the concept and principle of mercy contained in surah Ar-Rum verse 21 has principles that not only lead to the meaning of children but also other principles, such as the principle of getting calm, peace and harmony, and abstaining from actions that are not pleasing to Allah SWT which can be applied in marriage. On the other hand, to maximize the principles of rahmah, childfree or childless couples can realize it by adopting abandoned children who do not have parents as an alternative to achieving rahmah as a whole.Keywords :ContextualizationRahmah;Ar-Rum:21;Childfree;Childless